Incidence of gastro-esophageal reflux disease associated with type 2 diabetes - Tandukar, Sudarshan; Joshi, Ansu Mali (Journal of Universal College of Medical Sciences, 2015)
BACKGROUND: Gastro-Esophageal Reflux Disease is a growing problem with a reportedly increasing prevalence in type 2 diabetes patients. Despite this, study on the prevalence of Gastro-Esophageal Reflux Disease in Nepalese patients with type 2 diabetes is not available. The objective of this study is to determine the incidence of Gastro-Esophageal Reflux Disease in Nepalese patients with type 2 diabetes. MATERIAL AND METHODS: This cross-sectional study was carried out for a period of three months in patients with type 2 diabetes. A structured questionnaire “Frequency Scale for the Symptoms of GERD (FSSG)” was used for the evaluation of Gastro-Esophageal Reflux Disease in a total of Ninety Six (96) patients. RESULTS: The incidence of Gastro-Esophageal Reflux Disease was observed in 22% of the patients with type 2 diabetes. The mean FSSG score in patients with Gastro-Esophageal Reflux Disease was 15.2 ± 9.3. CONCLUSION: Gastro-Esophageal Reflux Disease is a common phenomenon in type 2 diabetes. Effective treatment along with proper glycemic control is essential so as to promote the Quality of Life of individuals.